Pensyariatan Puasa (Suatu Kajian Historis) - Abduh Muhammad (Al-'Adl, 2009)
Fasting is one of the oldest worship ever known to mankind. in a broad sense, fasting means restraint or abandonment of actions including eating, drinking, talking or moving to a place like that of Siti Maryam. But in a technical sense, fasting means refraining from eating, drinking, and sexual intercourse between husband and wife from the dawn of Sadiq to the sun, and accompanied by intent.According to experts, this fasting has been done since the prophet Adam. Then followed by the people of the next Prophets, even with the ordinances, the number of days and motivations vary.